ANALYSIS OF MARKET ORIENTATION AND FINANCIAL LITERACY ON MSME PERFORMANCE - Rijaldi, Sya'rony Muhammad; Sunarya, Erry; Ramdan, Asep Muhamad (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
MSME performance is the level of success achieved by MSME stakeholders in running their businesses based on set goals. To support the success of MSME performance, MSME owners must have basic knowledge such as market orientation and financial literacy because these two things can be a benchmark for the success of MSMEs. This study aims to analyze the influence of market orientation and financial literacy on the performance of food industry MSMEs in Sukabumi. The number of samples in this study was 110 respondents. This study used descriptive research methods and associative research methods with a quantitative approach. The results showed that market orientation and financial literacy had a positive and significant effect on MSME performance. The contribution made between market orientation and financial literacy to the performance of MSMEs with interpretation is very strong. Keywords: Market Orientation, Financial Literacy, MSME Performance